KEWENANGAN KEPOLISIAN NEGARA REPUBLIK INDONESIA ( POLISI PERAIRAN ) DALAM PEMBERANTASAN TINDAK PIDANA PELAYARAN OVERDRAFT DI TINJAU MENURUT UNDANG - UNDANG NOMOR 2 TAHUN 2002 TENTANG KEPOLISIAN NEGARA - Edy Sanjaya (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTCriminal offenses cruise is one of the criminal acts that occurred in the waters and a threat to the crew or passengers and cargo in the payload, and here the role of water police as acting principal in the waters of the competent prosecuting criminal offenses in accordance with the authority of the Police as contained in Article 16 of Law - Law No. 2 of 2002 on State police can make arrests, detentions, searches and seizure. Sailing criminal offense provisions set in the Law - Law No. 17 of 2008 on Shipping in Chapter XIX of Article 284 to Article 336. Enforcement will be undertaken in order to combat criminal acts cruise excessive overdraft or charge for the creation of law enforcement in the waters under the principles rule of law in Article 2 of Law - Law No. 17 of 2008 on the cruise